2020
DOI: 10.1002/ffj.3606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sterilization methods on pomegranate juice evaluated by descriptive sensory analysis and gas chromatography‐mass spectrometry through partial least‐squares regression

Abstract: Similar to the processing of other juices, sterilization is an indispensable operation in PG juice processing. In addition to inactivating microorganisms, different sterilization techniques including thermal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(74 reference statements)
3
5
0
Order By: Relevance
“…Linalool, responsible for the floral, citrus, and fruity aroma, was more damaged in the PJV sample and increased in the UJV sample. In the studies about the different effects on volatile compounds, as for the thermal pasteurization and ultrasound treatment applied to pomegranate juice, limonene compounds decreased in both treatments, as in our study (Tian et al, 2020). Thermal pasteurization affected the 2‐heptanone compound 38.1% more than ultrasound treatment ( p > 0.05).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Linalool, responsible for the floral, citrus, and fruity aroma, was more damaged in the PJV sample and increased in the UJV sample. In the studies about the different effects on volatile compounds, as for the thermal pasteurization and ultrasound treatment applied to pomegranate juice, limonene compounds decreased in both treatments, as in our study (Tian et al, 2020). Thermal pasteurization affected the 2‐heptanone compound 38.1% more than ultrasound treatment ( p > 0.05).…”
Section: Resultssupporting
confidence: 84%
“…At the end of the ultrasound applied to jujube vinegar, decreases in the octanal compound were similarly detected as the effect of ultrasound to removing bitterness in citrus fruit juice (Kumar Gupta et al, 2021). Tian et al, 2020 reported that ultrasound treatment preserved total alcohol volatile compounds more than thermal heat treatments, as in our study. Similar results were found for the thermosonication treatment applied to grape juice, with reductions in aldehyde compounds (Ma et al, 2020).…”
Section: Volatile Profilesupporting
confidence: 81%
“…A decrease in the octanal compound was detected after ultrasound treatment. In reports of different effects on volatile compounds of thermal pasteurization and ultrasound treatment applied to pomegranate juice, ρ-cymene compounds decreased in both treatments, as in our study [ 67 ]. Similar effects were also detected after ultrasound was used to remove bitterness in citrus juice [ 14 ].…”
Section: Resultssupporting
confidence: 83%
“…Heat treatment can trigger the oxidation of fatty acids under heat and air, leading to the increase of straight‐chain aldehydes. Tian et al (2020) and Bi et al (2020) found an increase of 449.53% ( R * = 3.35) and 188.84% ( R * = 2.88) of (E)‐2‐hexenal in thermal pasteurization treated pomegranate juice and orange juices, respectively. Tian et al (2020) also reported an increase of 235.13% ( R * = 5.49) of (E)‐2‐hexenal in high‐temperature short‐time treated pomegranate juice.…”
Section: Resultsmentioning
confidence: 97%
“…Degradation of aroma compounds is strongly influenced by heat and promoted at higher temperatures, and can also proceed through C‐C bond cleavage and elimination pathways (Mahanta et al, 2021). Tian et al (2020) reported a reduction of 70.51% ( R * = 0.29), 22.58% ( R * = 0.77), and 19.82% ( R * = 0.82) in concentrations of d‐limonene in pomegranate juices treated by thermal pasteurization, high‐temperature short‐time, and ultrasound, respectively.…”
Section: Resultsmentioning
confidence: 99%